The competences required by project managers for project success - Emmanuel Amemakalor (KNUST, 2025)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the Requirement for the award of Master of Science